2009
DOI: 10.1002/adsc.200900258
|View full text |Cite
|
Sign up to set email alerts
|

Samarium Powder‐Catalyzed Palladium‐Free and Ligand‐Free Sonogashira Coupling Reactions

Abstract: A study of samarium powder-catalyzed cross-coupling reactions of aryl halides with terminal alkynes is described. The couplings performed in the polyethylene glycol PEG-600 provided the corresponding coupling products in good yields. The first example of palladium-free, copper-free and amine-free catalytic system for Sonogashira couplings is presented in the absence of ligand.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 68 publications
(13 reference statements)
0
20
0
Order By: Relevance
“…While a number of transition metals, including Ag, Au, Co, In, Rh, Ru, and even rather scarce Sm, have occasionally been reported to possess a distinct catalytic activity in the Sonogashira cross-coupling [28,147], industrially relevant, cheaper Cu, Ni, and Fe experienced by far the most scientific attention. In the 1990s, Miura et al [9] have discovered that various aryl and vinyl iodides could be coupled with terminal alkynes in a Cu-catalyzed reaction at elevated temperatures in DMF or DMSO with added PPh 3 and base.…”
Section: Alkynylations Catalyzed By Other Transition Metalsmentioning
confidence: 99%
“…While a number of transition metals, including Ag, Au, Co, In, Rh, Ru, and even rather scarce Sm, have occasionally been reported to possess a distinct catalytic activity in the Sonogashira cross-coupling [28,147], industrially relevant, cheaper Cu, Ni, and Fe experienced by far the most scientific attention. In the 1990s, Miura et al [9] have discovered that various aryl and vinyl iodides could be coupled with terminal alkynes in a Cu-catalyzed reaction at elevated temperatures in DMF or DMSO with added PPh 3 and base.…”
Section: Alkynylations Catalyzed By Other Transition Metalsmentioning
confidence: 99%
“…Researchers have aimed at lowering the reaction cost by using cheap metals instead of palladium and metal NPs immobilized on solid supports. [84][85][86][87] Thus, the use of nickel catalyst in Sonogashira cross-coupling of aryl halides with terminal alkynes has attracted much attention. Besides, Ni complexes can simply switch among different oxidation conditions, which leads to remarkable catalytic cycles, high reactivity and promising performance.…”
Section: Introductionmentioning
confidence: 99%
“…[25] Wei's group explored Cu powder in the regio and stereoselective aminobromination of α,β unsaturated ketones. [26] In 2009, Mao et al reported samarium powder catalyzed Sonogashira reaction. [27] The important features of Sm are being stable in air, cheap and easy to handle.…”
Section: Introductionmentioning
confidence: 99%